2022
DOI: 10.1001/jamanetworkopen.2022.20379
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Procedures Among Adults Discharged to Hospice After Gastrointestinal Tract Surgery in California

Abstract: IMPORTANCE Hospice care is associated with improved quality of life and goal-concordant care.Limited data suggest that provision of hospice services after surgery is suboptimal; however, literature in this domain is in its nascency, leaving gaps in our understanding of patients who enroll in hospice after surgery.OBJECTIVE To characterize the transition to hospice after gastrointestinal tract surgery and identify areas that warrant further attention and intervention. DESIGN, SETTING, AND PARTICIPANTSThis retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
(103 reference statements)
0
2
0
Order By: Relevance
“…Elsewhere in JAMA Network Open , Greenberg et al leverage California Patient Discharge Data to characterize patients who enrolled in hospice after gastrointestinal tract surgery. The authors identified 2688 patients discharged to hospice after surgery for a digestive disorder in California between January 1, 2015, and December 31, 2019.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Elsewhere in JAMA Network Open , Greenberg et al leverage California Patient Discharge Data to characterize patients who enrolled in hospice after gastrointestinal tract surgery. The authors identified 2688 patients discharged to hospice after surgery for a digestive disorder in California between January 1, 2015, and December 31, 2019.…”
mentioning
confidence: 99%
“…The analysis by Greenberg et al reveals multiple opportunities to elicit patient values and discuss future care among patients with gastrointestinal tract cancer undergoing surgical intervention and suggests that such conversations should begin at the time of diagnosis and continue even after hospice discharge. Unfortunately, for this cohort, it is unknown whether these conversations occurred and whether patient values were respected.…”
mentioning
confidence: 99%